PENGARUH AROMATERAPI LEMON TERHADAP EMESIS GRAVIDARUM PADA IBU HAMIL TRIMESTER I: THE EFFECT OF LEMON AROMATHERAPY ON EMESIS GRAVIDARUM IN FIRST TRIMESTER PREGNANT WOMEN - Derliana Marya Sari; Wenny Indah Purnama Eka Sari; Derison Marsinova Bakara (Jurnal Online Dengan Open Journal System, 2024)
Pregnancy is a physiological process that has an impact on the health of the mother and fetus especially in the first trimester in between occur change three hormone on woman that is increase levels of estrogen, progesterone, and expenditure production human chorionic gonadotropin (HCG) hormone caused by acidity stomach so that trigger emergence of nausea vomiting was called Emesis Gravidarum. Non - pharmacological therapy that can applied on pregnant women with emesis gravidarum is Aromatherapy. Aromatherapy give variety effect for the inhaler, like serenity , freshness , even can help mother pregnant resolve nausea , wrong one oil effective aromatherapy in reduce nausea is lemon aromatherapy. The study used design Quasy experiments, with pre test and post test design with control group. Subject in study this was primigravida with complaints emesis gravidarum. Technique sample used consecutive sampling with total respondent 36 primigravida.. Test statistics use non- parametric test that is test Mc Nemar and test Fhister Exact. Results study this showed there is significant between two group with p value 0.000 (< 0.05), that there is effect of lemon aromatherapy to reduce emesis gravidarum in pregnancy. Lemon aromatherapy has been proven to be effective in reducing nausea and vomiting in pregnant women in early pregnancy. Recommended for midwife in resolve or reduce Emesis Gravidarum on mother first trimester pregnant use non- pharmacological / complementary therapy like Giving Lemon Aromatherapy.